EP418/#181 Outcomes of positive groin sentinel lymph node biopsies in vulvar squamous cell carcinoma and HPV status: a population based study. (4th December 2022) - Stewart, Kimberly; Jamieson, Amy; Holloway, Caroline; Proctor, Lily; Wei, Kelly; Hoang, Lien; Kong, Iwa; Kwon, Janice
Abstract : Objectives: The GROINSS-V II study identified a threshold of 2 mm in positive inguinofemoral sentinel lymph nodes (SN) in vulvar squamous cell carcinoma (VSCC) for guiding subsequent treatment. The objective of this study is to stratify isolated groin recurrence rate of SN micrometastases (ITC and ≤2 mm) versus macrometastases (>2 mm) in the context of HPV status. Methods: Retrospective population based cohort from British Columbia, Canada included patients diagnosed from 2005–2020 with VSCC and positive SN. Tumour HPV status (independent/dependent) was determined with p16 immunohistochemistry or differentiated VIN pathology. Radiotherapy plans were reviewed for dose and volumes. Results: There were 232 patients of whom 38 (16.4%) had positive SN, 21 (55%) of these had HPV independent disease. Average follow up was 51 months (6–172). There were 10 (26%) with micrometastases; 1 of 3 recurred in the groin after adjuvant inguinofemoral radiotherapy, and 0 of 7 recurred after inguinofemoral lymphadenectomy (IFL). There were 28 (74%) with macrometastases; 1 of 2 recurred in the groin with no adjuvant therapy, 4 of 13 with adjuvant radiotherapy alone, and 0 of 3 after IFL. There were 2 of 10 who had IFL and adjuvant radiation who recurred with both groin and distant disease within 6 months of diagnosis. All recurrences in the macrometastatic subgroup were HPV independent. Conclusions: Isolated groin recurrence rate after adjuvant radiation only with macrometastatic SN in VSCC is high, in keeping with GROINSS-V II findings. All groin recurrences in macrometastatic SN were in HPV independent tumours, implying need for alternate treatment in this subgroup.